Metabolites and Free Fatty Acids in Japanese Black Beef During Wet Aging - Shuji Ueda; Yuka Yoshida; Yuka Tateoka; Biniam Kebede; Masakazu Shinohara; Hiroki Nakanishi; Itsuko Fukuda; Yasuhito Shirai (Metabolites)
Background: Japanese Black beef is known for its high intramuscular fat content, an important factor in its distinctive Wagyu aroma. Wet aging, which involves vacuum-packing meat and storing it at low temperatures, enhances flavor, texture, and tenderness and is essential for maintaining and improving meat quality. In this study, changes in metabolites and lipid profiles were investigated during the wet aging of Japanese Black and Holstein beef. Methods/Results: Gas chromatography–mass spectrometry identified 113 metabolites in Japanese Black beef and 94 in Holstein beef, with significant increases in metabolites like aspartic acid and maleic acid over the aging period. Regarding lipid composition, total free fatty acids significantly increased with wet aging, with Japanese Black beef showing significantly higher concentrations of oleic and linoleic acids than Holstein beef. Additionally, lipid analysis by liquid chromatography–mass spectrometry revealed a reduction in specific phospholipids, particularly lysophosphatidylcholine (LPC) and lysophosphatidylethanolamine (LPE), with notable decreases in LPC (18:1), LPC (18:2), LPE (18:1), and LPE (18:2). Conclusions: These results suggest that wet aging influences the stability of membrane lipids, facilitating the degradation of phospholipids into free fatty acids, and improving the flavor of Japanese Black beef.